A Study on Bio-Medical waste Segregation Monitoring in a Tertiary Care Hospital at Telangana - Sachin Suresh Shinde1, Kishore Babu Marivina2, Shalini3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The most appropriate way of identifying the categories of healthcare waste is by sorting the waste into colorcoded plastic bags or containers.2,3 Since early recovery of patients and health of clinical staff directly depends on a clean and hygienic environment, excellent hygiene practices in health care facilities are the prerequisite for good medical waste management 8 Objective: Aim of this study is to see effectiveness of segregation practiced in the hospital and establish a monitoring system to monitor deficiencies in segregation. Method: This cross sectional study conducted during the period of June to August 2012 in a tertiary care Hospital. Eighty Two (82) areas were identified as BMW generation area. As per the norms segregation was done in four different color coded containers. So, total segregation containers will be 82X4=328. Any mix up or wrong segregation will be noted in the register daily by the Infection Control Nurse. A Monthly report based on BMW Register was developed. Results: The index named as Bio-Medical Waste Segregation Deficiency index (BMWSD index). calculated as number of deficiencies found in a area/areas divided by the possible number of deficiencies can occur in that area/areas. Daily data then entered into the Monthly report and monthly BMWSD index was made. Though this is a continuous process, for this study three months data (June, July and August 2012) were taken for analysis. Discussion: In this Cross sectional study, it was found that there was a over all deterioration in segregation of BMW when compare to June, July and August reports. The areas with high BMWSD index or where segregation is poor will be reflected through this monitoring system. Conclusion: This BMWSD index can be used as an indicator of Infection control Practice. This report is to identify the deficiency areas in the entire hospital in BMW segregation, which can be used for analysis and planning for better BMW Management like, training of the staffs of particular units, modification in methods etc.